Netralitas Asn Dalam Pilkada Bupati (Tinjauan Komunikasi Dalam Pengawasan Bawaslu Di Kabupaten Gowa) - Marwah, Marwah (Danudirja Setyabudi Nusantara, 2025)
This study aims to analyse the non-neutrality of civil servants in the 2024 regional head elections in Gowa Regency; communication in the supervision of the Gowa Regency Election Supervisory Agency (Bawaslu) to realise civil servant neutrality; and the actions of the Gowa Regency Bawaslu in handling violations of civil servant neutrality. The research method used was qualitative field research. The research approach used was organisational communication theory. The data sources were primary and secondary data. The data collection methods consisted of observation, interviews, and documentation. The results of the study show that the factors causing civil servants to be non-neutral in the 2024 regional head elections in Gowa Regency are pressure from the incumbent or candidates who support the incumbent; temptation, personal interests in positions or benefits; kinship or connections; and supervision that is not yet comprehensive and a lack of supervisory human resources. Bawaslu conducted communication in the form of socialisation, public education, participatory supervision through dialogue and seminars, coordination with local governments, BKD, and inspectorates, as well as media campaigns. In handling violations, Bawaslu issued appeal letters, processed reports, and enforced the law through coordination with the Integrated Law Enforcement Centre (Gakkumdu), the State Civil Service Agency (BKN), and related agencies. Overall, this study emphasises the importance of educational, coordinative, and participatory institutional communication, as well as the need to strengthen regulations and guidance for ASN to maintain bureaucratic neutrality. These efforts are strategic steps toward building a professional, independent, and integrity-driven bureaucracy in the implementation of regional elections.